2022
DOI: 10.1155/2022/3415999
|View full text |Cite|
|
Sign up to set email alerts
|

Construction and Computation of the College English Teaching Path in the Artificial Intelligence Teaching Environment

Abstract: Today, English is the world’s main international language and is widely spoken. In this context, the learning of English has long been valued by all countries. In addition, English plays an essential role in the process of economic globalization, specifically in the majority of countries where English is not the native language. At the same time, as China’s integration into the world grows, the importance of English has become more pronounced, and the demand for English language skills has increased. At presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Other learning tasks can be completed offline and evaluated by teachers. This is in line with the learning characteristics of learners in the new era and helps to build a new model of "Internet plus" language learning era [2].…”
Section: Artificial Intelligence and Language Teachingsupporting
confidence: 59%
“…Other learning tasks can be completed offline and evaluated by teachers. This is in line with the learning characteristics of learners in the new era and helps to build a new model of "Internet plus" language learning era [2].…”
Section: Artificial Intelligence and Language Teachingsupporting
confidence: 59%
“…In the context of Indonesian university students, where English is considered a foreign language, a bilingual approach is deemed the most suitable for teaching English (Glas & Cárdenas-Claros, 2013;Liu, 2022). This approach offers numerous benefits for learners, who are expected to acquire both language and content knowledge simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%